Two decades of fluorine chemistry in Cergy - Pytkowicz, Julien; Chaume, Grégory; Lensen, Nathalie; Chelain, Evelyne; Brigaud, Thierry (Comptes Rendus. Chimie, 2024)
The development of chiral fluorinated biomolecules such as amino acids, peptides and pseudopeptides is attracting considerable interest at the frontiers of organic synthesis and biological chemistry. We propose in this review an overview of our contributions to organofluorine chemistry in connection with biological applications and also asymmetric synthesis these past twenty years in Université de Cergy-Pontoise (now CY Cergy Paris Université).